Macroeconomic Dynamics and Institutional Integrity: An Econometric Analysis of The Determinants of Poverty in Indonesia 2005-2024 - Agustina Eka Harjanti (Journal of Business Crime, 2026)
Objective: This study aims to to analyze the effect of corruption on poverty levels by considering key macroeconomic factors as variables that provide theoretical contributions in the form of strengthening empirical evidence on poverty, as well as practical contributions in the form of more integrated policy recommendations to support inclusive, effective, and sustainable poverty reduction strategies.Research Design & Methods: The study used a quantitative approach with multiple linear regression methods on Indonesian time series data for the period 2005–2024. Classical assumption tests, including normality, heteroscedasticity, autocorrelation, and multicollinearity, were conducted to ensure the feasibility of the estimation model.Findings: The analysis shows that economic growth has a positive but insignificant effect on poverty, inflation has no significant effect, unemployment has a positive and significant effect, and CPI has a negative and significant effect on poverty. These findings confirm that structural factors such as unemployment and governance quality play a stronger role than other macro variables in explaining poverty dynamics in Indonesia.Implications: The results of the study indicate the importance of development policies that emphasize inclusive job creation, price stability accompanied by social protection, and strengthening the eradication of corruption in order to increase the effectiveness of poverty alleviation programs.Contribution & Value Added: This study provides latest empirical contributions regarding the simultaneous relationship between macroeconomic variables and corruption on poverty in the context of Indonesia over a long period, and confirms that improving governance and reducing unemployment are key strategies in reducing poverty in a sustainable manner.